2000
DOI: 10.1007/s10434-000-0021-1
|View full text |Cite
|
Sign up to set email alerts
|

Biopsy Method and Excision Volume Do Not Affect Success Rate of Subsequent Sentinel Lymph Node Dissection in Breast Cancer

Abstract: SLND has a high success rate in breast cancer patients regardless of the biopsy method or the excision volume removed before SLND. In addition, the interval from biopsy to SLND, tumor size, and tumor location have no effect on the success rate of SLND, even in this series which included patients operated on before the technique was adequately defined. Patients with breast cancers located in any quadrant and diagnosed either with a needle or excisional biopsy could be evaluated for trials of SLND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(57 citation statements)
references
References 21 publications
1
52
0
4
Order By: Relevance
“…Despite varying lymphatic mapping techniques used worldwide, identification rates remain consistently higher than 91%, with false negatives estimated at 8% 4 ; with more extensive experience, these rates approach 100% [5][6][7] and <5%, 7,8 respectively. A pathologically negative SLN is now widely accepted as reliably identifying the node-negative breast cancer patient who does not need to face the morbidity of a standard ALND.…”
mentioning
confidence: 98%
“…Despite varying lymphatic mapping techniques used worldwide, identification rates remain consistently higher than 91%, with false negatives estimated at 8% 4 ; with more extensive experience, these rates approach 100% [5][6][7] and <5%, 7,8 respectively. A pathologically negative SLN is now widely accepted as reliably identifying the node-negative breast cancer patient who does not need to face the morbidity of a standard ALND.…”
mentioning
confidence: 98%
“…Primer tümörün çapı arttıkça aksilladaki metastatik lenf nodu sayısının arttığı bildirilmiştir [20]. Bir çalışmada tümör çapı 3cm'nin altındaki tümörlerde aksillaya metastaz oranı %38 olarak bulunurken, 3-5cm arasındaki tümörlerde bu oran %55 olarak bulunmuştur [21][22][23].…”
Section: Discussionunclassified
“…[33][34][35] Recently, Haigh et al demonstrated that a previous excisional biopsy did not compromise successful identification of the sentinel lymph node. 53 Although the therapeutic perspectives for the ABBI method are limited at present by the small number of potential indications and the need for axillary lymph node staging for invasive lesions, this procedure may have a contributory role within the framework of the management of subclinical cancers. Stereotactic large-core breast biopsy, which is currently used to diagnose NPBL, provide fragmented tissue specimens and almost total disappearance of the tumor, when it is small.…”
Section: Discussionmentioning
confidence: 99%